Computed tomography and childhood seizure disorder in Ibadan (2004)
Background: Computed Tomography (CT) is an important tool for neuroimaging, it offers an opportunity to investigate structural lesion as a cause of seizures with little morbidity. This study is designed to evaluate its's applicability in children with epileptic seizures. Method: It is a descriptive study of the CT scans of the 103 consecutive children who were referred to the CT suite of the University College Hospital on account of seizure disorders over a 5 year period (1997-2001). Results: Only 103 (4.6%) of the subjects who had cranial scans done in five years were children with seizures disorders. The CT scans were abnormal in 53 (51.5%). Hydrocephalus was the most common finding in 14(13.6%). Cerebral atrophy and infarct were reported in 10.6% and 8.7% respectively. the outlined cranial fractures found in 6.8% were all depressed. A high incidence (74.4%) of abnormal scans was reported in the children with partial seizures. Thirty-three (62.3%) of the abnormal scans were amenable to surgery. The presence of neurologic deficit increased the yiled of abnormal CT features. Conclusion: CT scans are extreme value in the screening and difinitive evaluation of seizures in children. It is advocated for excluding treatable conditions and monitoring progression of the disorder.